2014
DOI: 10.1007/s11666-014-0206-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Aging Behavior of Axial Suspension Plasma-Sprayed Yttria-Stabilized Zirconia (YSZ) Thermal Barrier Coatings

Abstract: 7.5YSZ thermal barrier coatings (TBCs) were deposited onto the stainless steel substrates using axial suspension plasma spraying (ASPS). Free-standing coatings were isothermally aged in air from 1200 to 1600°C for 24 h and at 1550°C for 20 to 100 h, respectively. Thermal aging behavior such as phase composition, microstructure evolutions, grain growth, and mechanical properties for thermal-aged coatings were investigated. Results show that the as-sprayed metastable tetragonal (t 0 -ZrO 2 ) phase decomposes int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 28 publications
1
14
0
2
Order By: Relevance
“…The H and E values of the coating after being heat-treated at 1550 • C for 60 h reached maximum values of 11.1 ± 1.7 GPa and 188.4 ± 19.3 GPa, respectively, representing increases by approximately 66% and 97%, respectively, compared to the as-deposited coating. Similar trends of the H and E values of coatings have been reported previously; in particular, Zhao et al found that in axial suspension plasma spraying (ASPS) YSZ TBCs, the mechanical properties firstly increased significantly with sintering, and then decreased with prolonged thermal aging time, which was caused by a t-ZrO 2 → m-ZrO 2 phase transformation after thermal exposure at 1550 • C for 60 h [21]. Sintering can increase the H and E values due to thermal exposure, which has been reported for APS, ASPS and EB-PVD coatings [27][28][29].…”
Section: Mechanical Propertiessupporting
confidence: 82%
See 2 more Smart Citations
“…The H and E values of the coating after being heat-treated at 1550 • C for 60 h reached maximum values of 11.1 ± 1.7 GPa and 188.4 ± 19.3 GPa, respectively, representing increases by approximately 66% and 97%, respectively, compared to the as-deposited coating. Similar trends of the H and E values of coatings have been reported previously; in particular, Zhao et al found that in axial suspension plasma spraying (ASPS) YSZ TBCs, the mechanical properties firstly increased significantly with sintering, and then decreased with prolonged thermal aging time, which was caused by a t-ZrO 2 → m-ZrO 2 phase transformation after thermal exposure at 1550 • C for 60 h [21]. Sintering can increase the H and E values due to thermal exposure, which has been reported for APS, ASPS and EB-PVD coatings [27][28][29].…”
Section: Mechanical Propertiessupporting
confidence: 82%
“…Sintering can increase the H and E values due to thermal exposure, which has been reported for APS, ASPS and EB-PVD coatings [27][28][29]. For example, Zhao et al showed that the H and E values of ASPS TBCs increased by about 50% and 44% on the cross-section after 1300 • C/24 h exposure in air [21]. An early study on a plasma-sprayed TBC also reported that the E value of the ceramic coating increased after exposure, which was attributed to the healing of pores and grain growth and the improvement in bonding and coherence across the splat boundary during exposure at high temperature as a result of the sintering Coatings 2019, 9, 464 9 of 11 effect [30].…”
Section: Mechanical Propertiesmentioning
confidence: 83%
See 1 more Smart Citation
“…As a promising solution, suspension plasma spraying (SPS) facilitates the usage of nanostructured feedstock and the implementation of strain tolerant columnar or vertically cracked microstructures . These features are believed to improve the sintering resistance and mechanical performance of SPS TBCs, comparing to conventional air‐plasma‐sprayed (APS) coatings. Nevertheless, the sintering behavior of SPS TBCs remains to be further understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the poor sintering resistance of YSZ at higher temperatures reduces porosity in the top coat, deteriorating the thermal insulation ability of YSZ coating. It also increases the elastic modulus due to microstructure densification, causing the decrease of the strain compliance of YSZ coating [7][8][9].…”
Section: Introductionmentioning
confidence: 99%